Using Themes-Based Ontology for Learning Al-Quran Knowledge / Azman Ta'a ... [et al.] - Ta'a, Azman (UiTM Press, 2016)
Learning Al-Quran knowledge involves the classification of Al-Quran verses into a better understanding for the readers. This research aims to explore a themes based ontology approach to classify Quranic verses. Nowadays, Information and Communication Technologies (ICTs) are becoming increasingly important, which requires Quranic knowledge representation to be understood by both humans and computers. Efforts have been carried by many Muslim scholars and intellectuals in developing ICT applications for Islamic uses, and at the same time promote Islamic knowledge and information through ICT enabling tools which has become a driver for readers all over the world to collect, exchange, share and spread information about Islam. Current approaches use conventional methods to classify knowledge, such as taxonomy, hierarchy or tree structure, which only provides a concept definition without a link to other sources of knowledge. Therefore, due to the significant benefits of the theme based approach, this research uses a theme based classification approach to develop the Quranic Ontology. The ontology model for the Al-Quran was developed based on the Quranic knowledge themes which are defined in the "Syammil Al-Quran" ("Miracle the Reference"). Understanding the depth of Islamic knowledge and teaching needs an established academic method. On the other hand, learning Quranic knowledge through ICT has shown great impact on new learning methods for readers and has proved to be an effective way for enhancing the knowledge of the Al-Quran.